Association of Urinary Cadmium with Cancer Mortality Is Influenced by Zinc Intake in Follow-up Study of NHANES 1988–1994 and 1999–2004 (P18-026-19). (13th June 2019) - Kim, Kijoon; Melough, Melissa; Sakaki, Junichi; Noh, Hwayoung; Koo, Sung; Chun, Ock K
Abstract: Objectives: Exposure to cadmium (Cd), a toxic heavy metal, increases risk of numerous chronic diseases and overall mortality. However, little work has been conducted to examine the effect of Zn intake on the association between Cd burden and mortality. The aim of this study was to examine whether the association between urinary Cd concentration and all-cause and disease specific mortality differs by Zn intake level among a representative sample of the US adult population. Methods: A total of 15, 642 US adults aged 30 years and older in the National Health and Nutrition Examination Survey 1988–1994 and 1999–2004 were followed up through December 31, 2011. Participants' Zn intake was assessed through 24-hour dietary recalls. The main outcomes included mortality from cardiovascular disease (CVD), cancer, and all causes. Using Cox proportional hazards models, hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated for quartiles of urinary Cd, quartiles of dietary Zn, and for quartiles of urinary Cd stratified by level of dietary Zn. Results: Of 5367 total deaths that occurred over a mean follow-up of 15 years, 1194 were attributed to cancer and 1677 were attributed to CVD. After adjustment for potential confounders, positive relationships were observed between urinary Cd and all-cause mortality (HR for highest vs. lowest quartile (Q4 vs. Q1): 1.38; 95% CI: 1.14–1.68; P -trend < 0.0001) and cancer mortality (HR for Q4 vs. Q1: 1.54; 95% CI: 1.05–2.27; P -trend < 0.005), but not CVD mortality (HR for Q4 vs. Q1: 1.22; 95% CI: 0.95–1.57; P -trend = 0.0502). Negative associations were observed between dietary Zn and all-cause mortality (HR for Q4 vs. Q1: 0.88; 95% CI: 0.75–1.02; P -trend < 0.05) and cancer mortality (HR for Q4 vs. Q1: 0.82; 95% CI: 0.65–1.03, P -trend < 0.05). Among the lowest tertile of Zn consumers, there was a clear positive association between urinary Cd and cancer mortality (HR for Q4 vs. Q1: 1.79; 95% CI: 1.07–3.01), however, among the highest Zn consumers, this association was somewhat diminished (HR for Q4 vs. Q1: 1.66; 95% CI: 0.80–3.41). Conclusions: These findings support existing evidence that Cd burden is associated with greater mortality, and also demonstrate that greater Zn consumption is associated with reduced risk of cancer death related to Cd. Funding Sources: This study received no financial support.